COVID-19: ICTs, Tearing the veil of social inequality in Education - Anderson , Lucía (2022)
The COVID-19 crisis has wounded society in different areas, such as social, economic, but particularly, the educational field as a result, of the great economic inequality of social groups in the face of the educational process and, particularly, access to technology. The clearest effect revealed during the crisis is the weaknesses of educational policies, not only at the national level, but also at the global level. Vulnerability and social inequality became even more latent in this global crisis, with disadvantaged groups being, once again, the most affected. The purpose of this article is to examine the bleak effect of the Covid-19 pandemic, especially as it relates to humanity's coexistence. Although the appearance of ICT has transformed and connected us on a worldwide level, producing a feeling of closeness, this has only been a mirage which disguises negligence on both a governmental level as well as an educational level. The need for changes to generate an egalitarian educational system--one which doesn't economically favor some over others-- is, without doubt, a priority.